2015
DOI: 10.12705/644.8
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships among Dorema, Ferula and Leutea (Apiaceae: Scandiceae: Ferulinae) inferred from nrDNA ITS and cpDNA noncoding sequences

Abstract: Dorema, Ferula and Leutea are genera of Apiaceae tribe Scandiceae, subtribe Ferulinae. Their placement in Scandiceae was established based only on nuclear ribosomal DNA internal transcribed spacer (nrDNA ITS) sequence variation. Previous molecular studies suggested that Dorema and Leutea are nested within Ferula. To confirm relationships and eventual nomenclatural changes, we increased taxonomic sampling and examined nrDNA ITS and three noncoding cpDNA markers: rpoB‐trnC intergenic spacer and rps16 and rpoC1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…Therefore, for a representative set of accessions comprising 18 genera and 59 species of Daucinae we also included three chloroplast markers, the rpoC1 and rps16 introns and the rpoB-trnC intergenic spacer. These markers have already been employed in phylogenetic analyses of umbellifers Downie & al., 2000b;Calviño & al., 2010;Panahi & al., 2015).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, for a representative set of accessions comprising 18 genera and 59 species of Daucinae we also included three chloroplast markers, the rpoC1 and rps16 introns and the rpoB-trnC intergenic spacer. These markers have already been employed in phylogenetic analyses of umbellifers Downie & al., 2000b;Calviño & al., 2010;Panahi & al., 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The rps16 intron was amplified using external primers 5exonC and 3exonR from Calviño & al. (2006) or s16exF and s16exR from Panahi & al. (2015); additionally, two internal primers, s16inF and s16inR were also used (Panahi & al., 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferula violacea Korovin and F. olivacea (Diels) H. Wolff. were chosen as outgroup taxa after Panahi et al (2015). Maximum parsimony (MP) analysis of the ITS dataset was performed with PAUP* (Swofford 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Spalik and Downie integrated the whole Leutea species into the genus Ferula (see Kurzyana-Mlynik et al 2008). Recent works of Panahi et al (2015) suggested that species of Leutea should be re-established from Ferula again.…”
Section: Introductionmentioning
confidence: 99%